ANALISIS TINGKAT KENYAMANAN SISWA KELAS V DALAM KEGIATAN MEMBACA DIAM (SILENT READING) DI SDN 3 MEKARJAYA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of student comfort in silent reading to support concentration and interest. However, many students at SDN 3 Mekarjaya initially showed restlessness and lack of focus during these activities. This study aims to determine the comfort level of fifth-grade students in silent reading at SDN 3 Mekarjaya. The methodology employed is quantitative research using a survey method. The research population consisted of 21 fifth-grade students, with the sample determined through total sampling. Data were collected via a closed Likert-scale questionnaire comprising 27 valid items with a very high reliability coefficient of 0.983. Data analysis involved descriptive statistics, including mean, median, mode, frequency distribution, variance, and standard deviation. The results indicate that the comfort level of fifth-grade students in silent reading is generally in the "Very Comfortable" category, with 10 students (47.6%) being very comfortable, 9 students (42.9%) comfortable, 1 student (4.8%) moderately comfortable, and 1 student (4.8%) very uncomfortable. In conclusion, fifth-grade students at SDN 3 Mekarjaya feel very comfortable during silent reading activities, influenced by physical factors such as lighting and room temperature, as well as social factors including positive interactions with teachers and peers.